Women in British Nonconformity, circa 1880-1920, with special reference to the Society of Friends, Baptist Union and Salvation Army - Lauer, L (1997)
The reclamation and analysis of women's experiences within three Nonconformist denominations is the focus of this thesis. The first chapter places each denomination in its social and theological context, and describes its governing structures. The bulk of the thesis is devoted to situating women within this context and examining the ways in which women sought representation within male-dominated governing structures. Chapter two examines the conflict between Friends' egalitarian theology and women's lack of governing power. Although women Friends gained access to the governing body of the Society, the issue of equality remained problematic. The chapter finishes with a discussion of the Society's split over women's suffrage. The Baptist Zenana Mission is the focus of the third chapter. Zenana missionaries claimed spiritual and imperial authority over "native" women and used the languages of separate spheres to carve out a vocation for single women in keeping with denominational norms. In so doing, they marginalised the work done by missionary wives. The fourth chapter begins with an examination of the life and theology of Catherine Booth, whose contribution to the Salvation Army is often neglected. Catherine advocated women's ministry in terms that validated both "women's work for women" and public preaching. This chapter looks at the appeal of officership for women, especially the empowering experiences of salvation and holiness, and charts the growth of the Women's Social Work. Despite the Army's egalitarian theology, conflict was felt by women officers who struggled to combine corps and family duties. The final chapter briefly examines idealised representations of women to conclude that their defining power, while significant, was by no means hegemonic.